From Land to Labor How Governance Sustains Territorial Maximalism Despite Peace Processes - Muhammad Ramadhanta Sayeed Hermanda; Windy Dermawan (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This manuscript does not aim to resolve ideological, historical, or religious claims over territory. Instead, it examines how contemporary forms of power shape protracted conflict through governance mechanisms that regulate land, labor, and resources. Drawing on conflict transformation theory, political economy, and critical governance studies, the article argues that dominant peace frameworks—centered on territorial partition, security coordination, or economic cooperation—are structurally limited because they leave asymmetric governance arrangements intact. These arrangements enable control without political integration, allowing domination to persist even in the absence of formal annexation. By reframing territorial maximalism as a governance project rather than a purely ideological aspiration, the study demonstrates how expansionist ambitions are operationalized through regulatory authority over space, mobility, and economic life. The case illustration of Jericho shows how localized stability and development initiatives can coexist with deep structural dependency when governance authority is not shared. Economic activity and administrative capacity, often interpreted as indicators of progress, may instead stabilize unequal power relations. To address these limitations, the article advances the concept of cooperative territorial governance as a pathway for conflict transformation independent of final-status agreements. By institutionalizing shared authority over labor regulation, land use, and resource management, this framework challenges governance-based domination and offers a pragmatic foundation for transforming the structural conditions sustaining modern territorial conflicts.